Representations as mediation between purposes as junior secondary science students learn about the human body. Issue 2 (22nd January 2018) - Olander, Clas; Wickman, Per-Olof; Tytler, Russell; Ingerman, Åke
ABSTRACT: The aim of this article is to investigate students' meaning-making processes of multiple representations during a teaching sequence about the human body in lower secondary school. Two main influences are brought together to accomplish the analysis: on the one hand, theories on signs and representations as scaffoldings for learning and, on the other hand, pragmatist theories on how continuity between the purposes of different inquiry activities can be sustained. Data consist of 10 videotaped and transcribed lessons with 14-year-old students ( N  = 26) in Sweden. The analysis focused instances where meaning of representations was negotiated. Findings indicate that continuity is established in multiple ways, for example, as the use of metaphors articulated as an interlanguage expression that enables the students (and the teacher) to maintain the conversation and explain pressing issues in ways that support of the end-in-view of the immediate action. Continuity is also established between every day and scientific registers and between organisation levels as well as between the smaller parts and the whole system.